Hearing parents and deaf children: is the role of families in bilingual educational proposals - Ribeiro, Viviane Lameu; Leite Barbosa, Raquel Lazzari [UNESP]; Sartoreto Oliveira Martins, Sandra Eli [UNESP] (Univ Federal Santa Maria, 2019)
From the late twentieth century, researches intensify discussions about the foundational role of Sign Language in the educational development of deaf child. In Brazil, Brazilian Sign Language - Libras was officially recognized as the first language of the deaf community and its use and diffusion are guaranteed by legal documents that, in the same sense, provide for the education of the deaf to occur in a bilingual context. Deaf children born into deaf parents homes interact in Sign Language, naturally, like listeners in the auditory-oral language. Therefore, deaf children of hearing parents face difficulties in relating to family members if there is no opportunity to appropriate Sign Language at the suitable time, what interfers negatively in their linguistic and educational development. Although the role of family is made clear and established in legal documents and specific guidelines of the Ministry of Education and the Secretariat of Special Education, regarding the importance of Sing Language learning by family members, programs designed for this purpose, are goals to be pursued by Brazilian Schools. In this way, this study aims to analyze such implications, expanding the discussion about the need to offer family actions in bilingual educational programs that, among other aspects, defend the deaf child's right to interact in the world in/through Libras. In view of the above, it is believed that the Norwegian program Se mitt sprak (See my language) can be a relevant reference for future and urgent actions in this regard, which could be verified based on qualitative analysis of observations and written records, through Diary Research, as well as promotional materials and report of the program, collected during a study group visit to that country, sponsored by the Rotary International Foundation.
Keywords: Language; Deafness; Family